(untitled) (Editora Impacto Científico, 2025)
Academic Leagues, often treated as complementary activities, prove to be formative devices capable of shifting learning from the classroom to the lived world of care. This narrative review, anchored in existential phenomenology, mapped extension practices, described the experiences of students, preceptors, and the community, and interpreted emerging formative meanings. The search included national productions in health and related fields (2010–2025), prioritizing experience reports, essays, and reviews. The thematic synthesis highlighted three axes: i) repertoire of actions in the territory (health education, home visits, action research, teaching-service-community integration); ii) lived experience as situated, interprofessional, and relational learning, with an emphasis on communication, deliberation under uncertainty, and care coordination; iii) formative meanings interpreted as being-with, responsibility, the corporeality of learning, and the temporality of the project. Recurring fissures also emerged: institutional discontinuity, dependence on a small number of faculty, and assessment centered on workload. The conclusion is that, when intentionally mediated and anchored by university-service pacts, the Leagues consolidate student leadership, broaden the understanding of territory, and strengthen a user-oriented professional identity, shifting training from technical accumulation to a way of inhabiting care for others. DOI: https://doi.org/10.56238/edimpacto2025.090-021